Psychische Erkrankungen in der Arbeitswelt Analysen und Ansätze zur therapeutischen und betrieblichen Bewältigung - Alsdorf, Nora (Forschung aus der Hans-Böckler-Stiftung, 2017)
Which work situations are emotionally challenging? How do organizations deal with mental disorders? And how is work made a subject of discussion in therapy? The authors analyze the cases of employees suffering from mental disorders interdisciplinarily and show what options for improvement there are at the interfaces of the health system and the reintegration to the work place.